Efektywność bankowości hipotecznej i perspektywy jej rozwoju w gospodarce polskiej - Sitek, Marcin (Efficiency of Hypobank and Its Development Perspectives in Polish Economy, 2005)
This article presents arising and activity of hypobank in Poland, as well as efficiency of its activity in the range of hypocredit in comparison with universal banks. The trial of presentation of elements influencing the perspective evolution of hypobank in Poland is taken. The comparison of Polish hypobank system with solutions applied in UE and the world trends in the range of investments financing into real estate is made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 370-385